PREDICTIVE PARAMETERS FOR SUCCESSFUL FUNCTIONAL MATURATION OF NATIVE ARTERIOVENOUS FISTULA - Jamil, Muhammad; Usman, Rashid (Journal of Ayub Medical College Abbottabad, 2015)
Background: Successful arteriovenous fistula (AVF) significantly reduces both the morbidity as well as mortality of the patients who have end stage renal disease, and significantly improve their survival rate. The objective of the study was to high light the role of various parameters in the functional maturation of arteriovenous fistula (AVF). Methods: This descriptive analytical study conducted at Department of Vascular Surgery, Combined Military Hospital Lahore from January 2014 to January 2015. All consecutive patients who underwent creation of AVF and had pre and post-operative Duplex scan to assess the arteries and veins of the upper limbs, were included. The AVFs were created at wrist, forearm and arm under local anaesthesia. The data was collected from radiology department and dialysis centre and correlated with the data from operation theatre. Results: A total of 127 patients (89 males and 38 females) were included in this study. Only 57.5% (n=73) patients showed functional maturation of their AVFs. Of these, only 14 (36.8%) were females. Arterial and venous diameters of more than 2.5 mm (p=0.0001 and 0.001 respectively), fistulae created at elbow (p=0.001), presence of on-table thrill (p=0.003), presence of on-table bruit (p=0.001), patients having their AVFs created before the start of dialysis (p=0.0037) and kidney transplant (p=0.0042) were all positive predictors for successful functional maturation of AVFs. Female gender was a negative predictor and was responsible for non-maturation (p-value 0.003). Conclusion: Maturation of AVFs is a complex process influenced by a lot of factors. Although in our study various parameters proved to have positive impact on AVFs maturation, large prospective multi-centre studies are needed to provide well defined outcome.